Please help with this problem . Break it down for me 15-1/6n=1/6n-1
2 answers:
Math: Step 1: Simplify both sides of the equation. Simply steps provided. <span>15−1/6n=<span>1/6n−<span>1 </span></span></span><span><span>15+−1/6n</span>=<span>1/6n+−1 </span></span><span><span>−1/6n+15</span>=<span>1/6n−<span>1 </span></span></span><span>Step 2: Subtract 1/6n from both sides. </span><span><span><span><span>−1/6</span>n</span>+15</span>−<span>1/6n</span></span>=<span><span><span>1/6n</span>−1</span>−<span>1/6<span>n </span></span></span><span><span><span><span>−1/</span>3</span>n</span>+15</span>=<span>−<span>1 </span></span> Step 3: Subtract 15 from both sides. -1/3n = -16 Step 4: Multiply both sides by <em> </em>-3 -1/3 by 16.Your answer is: n = 48
15-1/6n=1/6n-1 First, lets multiply both sides by 6 so that n is a whole number: 90-n=n-6 now you group like terms on each side, to do this you add n to each side and add 6 as well so it becomes: 96=2n Now divide both sides by 2 so you have 'n' on one side and it is: 48=n Hope this helps :)
You might be interested in
Answer:
x=4
Step-by-step explanation:
2x-3=5
Add 3 to both sides
2x=8
divide both sides by 2
x=4
Answer:
1,40
Step-by-step explanation:
Answer:
Cool
Step-by-step explanation:
Your answer will be 10 dollars.
Answer:
1.4 ,0.667
Step-by-step explanation:
14/10 or